Kepuasan Pengguna Jasa Pada Kualitas Pelayanan KBIHU Al Mabrur Multazam Banyuwangi - Nur Roikhatul Jannah; Husna Ni’matul Ulya (Institut Agama Islam Negeri Ponorogo, 2023)
The enthusiasm of Muslims in Indonesia in carrying out Hajj from year to year has significantly increased the number of pilgrims. It is recorded that the number of pilgrims who will depart in 2023 is 221,000 people, consisting of 203,320 regular quota pilgrims and 17,680 special quota pilgrims. From the data details, the existence of KBIHU (Hajj and Umrah Guidance Group) Al Mabrur Multazam Banyuwangi is needed to create pilgrim satisfaction from the quality of services provided. This study uses a qualitative descriptive method, where writing provides an overview and presents data using interviews, observation, and research documentation techniques. The results of the research can be concluded that, in general, the quality of Hajj and Umrah services provided by KBIHU Al Mabrur Multazam Banyuwangi has been carried out well because it carries out the dimensions of service quality, namely Compliance with Islamic Sharia (Sharia Compliance), Assurance (Assurance), Reliability (Reliability), Physical Evidence (Tangible), Attention (Empathy), and Responsiveness (Responsiveness). However, it is necessary to add mentors to provide maximum service and positively impact service quality on pilgrim satisfaction.